2016
DOI: 10.1155/2016/2641876
|View full text |Cite
|
Sign up to set email alerts
|

Bilateral Non-Hodgkin’s Lymphoma of the Temporal Bone: A Rare and Unusual Presentation

Abstract: Primary lymphoma of the temporal bone is an unusual finding in clinical practice and bilateral affection is even more rare. To the best of our knowledge, there are no reports of bilateral primary temporal bone lymphoma without middle ear involvement in the English medical literature so far. We report, for the first time, a case of primary lymphoma involving both temporal bones which presented with left-sided infranuclear facial palsy. A combination of contrast enhanced magnetic resonance imaging (MRI) and high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 12 publications
1
13
0
Order By: Relevance
“…The follicular, small cleaved‐cell type are considered low grade with a 5‐year survival rate of 70%, however, DLC types of NHL are considered high grade and 5‐year survival of DLBCL is about 30%, as our patient passed away in the second year of diagnosis . Some authors reported that the pathological evaluations revealed positive for CD20 and the high percentage of Ki67 for diagnosis of DLBCL …”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…The follicular, small cleaved‐cell type are considered low grade with a 5‐year survival rate of 70%, however, DLC types of NHL are considered high grade and 5‐year survival of DLBCL is about 30%, as our patient passed away in the second year of diagnosis . Some authors reported that the pathological evaluations revealed positive for CD20 and the high percentage of Ki67 for diagnosis of DLBCL …”
Section: Discussionmentioning
confidence: 84%
“…26 Some authors reported that the pathological evaluations revealed positive for CD20 and the high percentage of Ki67 for diagnosis of DLBCL. 27,28 It is challenging to detect primary DLBCL when it affects more than one organ of a human body. Even though it is rarely seen in the oral region, clinicians should keep in mind that differential diagnosis of these lesions is very difficult when other lesions are involved or related.…”
Section: Discussionmentioning
confidence: 99%
“…A report suggested that a layer of lymphoid tissue located deep to the epithelium of the mucosa lining the mastoid antrum, tympanic cavity, and tympanic orifice of the eustachian tube acts as the site of origin of the primary lymphoma. [23] CT/magnetic resonance imaging is essential for highly suspected ear lymphoma. Of course, a definitive diagnosis should always be based on pathologic examinations.…”
Section: Discussionmentioning
confidence: 99%
“…These tumors arise from its various components including muscle, fascia, vessels, bones, nerves, and skin. Temporal bone tumors represent only 0.2% of head and neck cancers, 1 and temporal fossa tumors are not widely found in the English literature.…”
Section: Introductionmentioning
confidence: 99%